Business, Hospitality, and Change in Cuba's Private Tourism Sector: A View from Casas Particulares in Viñales. Issue 3 (4th May 2018) - Simoni, Valerio
ABSTRACT: Based on ethnographic fieldwork carried out in the town of Viñales, this article addresses some key features, stakes and debates that characterize privately run tourist accommodations known as casas particulares, including important (dis)continuities in their evolution in the last decade. Praised by tourists as a way to experience the "real" Cuba and establish closer contact with Cubans, casas particulares exemplify the burgeoning private tourism sector on the island. In Viñales, their number has increased dramatically in recent years, engendering changes that have become a heated issue of debate among the town's inhabitants. Examining the economic and social dimensions that characterize this form of tourist accommodation, its current developments, and their perceived impact on everyday life in Viñales, the article considers the tensions between ideals of hospitality and more business-oriented endeavours, uncovering the emerging controversies and moral economic critiques articulated by proprietors, tourists, and other inhabitants of this tourist town.